2019
DOI: 10.1111/ajt.15256
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of international living kidney donation in the United States

Abstract: The analyses described here are the responsibility of the authors alone and do not necessarily reflect the views or policies of the Department of Health and Human Services, nor does mention of trade names, commercial products or organizations imply endorsement by the U.S. Government. The data reported here have been supplied by the Minneapolis Medical Research Foundation (MMRF) as the contractor for the Scientific Registry of Transplant Recipients (SRTR). The interpretation and reporting of these data are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…From a program perspective, it is worth noting that OPTN policy‐compliant donor follow‐up was substantially lower for international living donors at 6, 12, and 24 months postdonation (2015 cohort: 45%, 33%, and 36% compared to 76%, 71%, and 70% for domestic living kidney donors, P < .001) . Transplant programs, especially small‐volume programs, should be aware of the possible adverse impact of accepting international donors on the program's follow‐up performance metrics…”
Section: Postdonation Care and Follow‐upmentioning
confidence: 99%
See 3 more Smart Citations
“…From a program perspective, it is worth noting that OPTN policy‐compliant donor follow‐up was substantially lower for international living donors at 6, 12, and 24 months postdonation (2015 cohort: 45%, 33%, and 36% compared to 76%, 71%, and 70% for domestic living kidney donors, P < .001) . Transplant programs, especially small‐volume programs, should be aware of the possible adverse impact of accepting international donors on the program's follow‐up performance metrics…”
Section: Postdonation Care and Follow‐upmentioning
confidence: 99%
“…Approximately 100‐150 LDKT from persons who are neither US citizens nor US residents (“international donors”) are performed in the United States each year . In 2015‐2016, the most frequent countries of origin for persons serving as international kidney donors in the United States were Mexico (N = 55), Kuwait (N = 22), Canada (N = 16), India (N = 16), Qatar (N = 15), the Dominican Republic (N = 14), the Philippines (N = 11), and the United Arab Emirates (N = 10); 63 other countries were represented, including 29 countries with a single donor each . Generally, international donors are family members or friends of patients with ESKD who visit the United States to serve as living kidney donors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 A recent study of US Organ Procurement and Transplantation Network (OPTN) registry data reported that international living kidney donors (ILKDs) were predominantly performed by a small number of transplant centers. 9 Better understanding of the challenges faced in assessment and care of ILKD candidates and donors may improve consideration of ILKD for US kidney patients, but to date, the nature of these challenges, and strategies to address them, have not been well described.…”
Section: Introductionmentioning
confidence: 99%